Hubungan Dukungan Keluarga dengan Kepatuhan Minum Obat dan Kontrol Diit Penderita Hipertensi - Sulistyana, Caturia Sasti (Jurnal Kesehatan Holistic, 2019)
Hypertension is an one of type degenerative disease which prevalence is increasing with the times. The success of managing hypertension is influenced by the patient's adherence to taking medication and maintaining a dietary habit. The purpose of this study was to determine the relationship of family support with adherence to taking medication and control of dietary in patients with hypertension. This research design used cross sectional to the sample of 30 hypertensive patients in RT VIII RW X Randu Agung 1, Kenjeran District, Sidotopo Wetan, Surabaya with simple random sampling technique. Analysis this research data used Chi-Square test. The results of the statistical test showed that p<0.05 (0.00), it describe a relationship between family support with adherence to taking medication and control of patients with hypertension. Compliance with the therapy program for a long period of time causes sufferers of hypertension to be susceptible to saturation and thus require need family support. The family is the closest environment that can provide care to improve the physical comfort and resilience of hypertensive patients so that they can be a major supporter in the treatment of diseases. Family support can increased the enthusiasm of patients to deal with the disease by providing motivation to control to the doctors and take medication regularly. The results of this study expected to increase self-awareness of hypertensive patients to improve compliance with their treatment so that their blood pressure remains normal and as a basis for developing further research.